Uses of Bacteriophages as Bacterial Control Tools and Environmental Safety Indicators - Rogovski, Paula; Cadamuro, Rafael Dorighello; da Silva, Raphael; de Souza, Estêvão Brasiliense; Bonatto, Charline; Viancelli, Aline; Michelon, William; Elmahdy, Elmahdy M.; Treichel, Helen; Rodríguez-Lázaro, David; Fongaro, Gislaine (Frontiers in Microbiology, 2021)
Bacteriophages are bacterial-specific viruses and the most abundant biological form on Earth. Each bacterial species possesses one or multiple bacteriophages and the specificity of infection makes them a promising alternative for bacterial control and environmental safety, as a biotechnological tool against pathogenic bacteria, including those resistant to antibiotics. This application can be either directly into foods and food-related environments as biocontrol agents of biofilm formation. In addition, bacteriophages are used for microbial source-tracking and as fecal indicators. The present review will focus on the uses of bacteriophages like bacterial control tools, environmental safety indicators as well as on their contribution to bacterial control in human, animal, and environmental health.